Necesidad de incorporar en el código penal y de procedimiento penal disposiciones que permitan el aborto provocado mediante autorización judicial en el caso de violación a mujeres discapacitadas mentalmente - Salazar Albán, Miguel Ángel (2014)
Sexual abuse within this sector is mainly driven by the unequal position of power and control, where people with disabilities are easy to manipulate and undermine as lacking, in most cases, opportunities to report abuse by barriers physical, sensory, intellectual or even institutional. This research is titled: "NEED TO INCLUDE IN THE CRIMINAL CODE OF CRIMINAL PROCEDURE RULES ALLOWING THE ABORTION CAUSED BY JUDICIAL AUTHORIZATION IN THE CASE OF RAPE WOMEN MENTALLY DISABLED". One that addresses the problems related to the rape of disabled women; further analyzes the Penal Code and Criminal Procedure under Ecuadorian law. The hypothesis that I lead is you work research was: "The lack of regulations in the Penal Code, which induced abortion to women with mental disabilities who have been sexually violated by judicial authorization and thereby solve a problem is allowed family and social" The processes used were hypothetical, inductive - deductive method, analytical explanatory, statistical; for the preparation of the descriptive analysis method was used. The techniques were applied was the survey of 30 practitioners in the free exercise of the city of Loja, through the instrument consisted of questions designed to obtain relevant information. Among the outstanding results we have through the study and legal and legal analysis of the issues raised, it is shown that there are flaws in the law, in relation to the Criminal Code and Criminal Procedure under Ecuadorian law, so necessary modify or update the Act, in order not to harm the mentally disabled women.